2003
DOI: 10.1024//1016-264x.14.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Receptive Amusia Suggests Functional Reorganization of Music- Processing Networks

Abstract: A follow-up study was performed in patients suffering from receptive amusia due to unilateral cerebrovascular cortical lesions. Perceptual musical functions had initially been assessed within the 5th and 10th day post-lesion and were re-evaluated 6-12 months after brain-damage. The standardized test battery covered local and global strategies of music perception in discrimination tasks. Retest sessions showed an overall improvement of music perception, reaching a significant group effect over all tasks. Marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…For amusia, this has been demonstrated in a study by the same group [4]. Similarly, in an earlier behavioural study no more auditory deficit was found after 1 year in two out of eight patients suffering from severe amusia, demonstrating compensating functional neuroplasticity [5].…”
supporting
confidence: 55%
“…For amusia, this has been demonstrated in a study by the same group [4]. Similarly, in an earlier behavioural study no more auditory deficit was found after 1 year in two out of eight patients suffering from severe amusia, demonstrating compensating functional neuroplasticity [5].…”
supporting
confidence: 55%
“…Later, brain reorganization and neuroplastic effects obscure the primary deficits. This is one of the reasons why, in a related study, recovery from amusia was a common finding ( Schuppert et al, 2003 ). To investigate the dependence of musical perception and expression on the temporal auditory areas, we decided to include only lesions with a focused area in the temporal lobe in one hemisphere.…”
Section: Discussionmentioning
confidence: 92%
“…The evaluation of musical functions is mainly suited to patients with a small lesion, who are less widely affected than those with other stroke-associated deficits of the motor and speech system. Given the near complete recovery of receptive musical deficits ( Schuppert et al, 2003 ), the use of a standardized diagnostic tool during the routine on a stroke unit is questionable. But for a more limited use with those patients complaining about a receptive or expressive musical deficit and especially for professional musicians such a battery could be meaningful.…”
Section: Discussionmentioning
confidence: 99%